MXene/Li4Mn5O12 nanocomposite electrocatalysts for boosting oxygen evolution reaction - Ritu Raj; Sunil Kumar; Vikash Kumar; Krishna Kanta Haldar; Gajendra Prasad Singh (Nano Express)
This study presents the synthesis and characterization of MXene/Li _4 Mn _5 O _12 nanocomposite electrocatalysts for enhanced oxygen evolution reaction (OER) performance. Through a systematic synthesis approach, we successfully integrated Ti _3 C _2 T _x MXene with Li _4 Mn _5 O _12 in varying compositions. The optimized MLMO50 nanocomposite demonstrated exceptional electrocatalytic activity, requiring only 282 mV overpotential to achieve 10 mA cm ^−2 current density, significantly outperforming pristine MXene (415 mV) and Li _4 Mn _5 O _12 (380 mV). The composite exhibited a favorable Tafel slope of 97 mV dec ^−1 and remarkably low charge transfer resistance of 116.4 Ω, indicating enhanced reaction kinetics. Comprehensive characterization using XRD, ATR-FTIR, FESEM, and XPS confirmed the successful synthesis and revealed the intimate interfacial interaction between MXene sheets and Li _4 Mn _5 O _12 . The MLMO50 catalyst showed excellent stability, maintaining performance over 3000 consecutive cycles with minimal overpotential shift (13.68 mV) and demonstrating robust durability during 15 h chronoamperometry testing. This work provides valuable insights into designing efficient composite electrocatalysts for clean energy applications.